The Spiritual Dimension of Caring: Applying a Model for Spiritual Tasks of Ageing - MacKinlay, Elizabeth (Journal of religious gerontology, 2002)
This chapter describes a spiritual dimension of ageing using themes and a model for spiritual tasks of ageing, developed as a part of doctoral studies that examined spirituality amongst a group of independent-living older adults in Canberra and NSW. This model has been tested further and the model was confirmed through in-depth interviews of residents of nursing homes in the ACT. The first study identified six major spiritual themes from participant interviews. These were: ultimate meaning in life for each person, the way they responded to meaning, self-sufficiency versus despair, moving from provisional to final life meanings, relationship versus isolation in ageing and hope versus despair.